Nurnajat won the first ever PUSPANITA Community Care Award - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 18 November- The first ever recipient of PUSPANITA Community Care Award at the 12th Universiti Malaysia Pahang Convocation Ceremony, Nurnajat Nadira Abdul Rahman, 24, contributed her success to the undying support from both her parents.